2019
DOI: 10.1016/j.cell.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

exRNA Atlas Analysis Reveals Distinct Extracellular RNA Cargo Types and Their Carriers Present across Human Biofluids

Abstract: Graphical Abstract Highlights d The exRNA Atlas provides access to human exRNA profiles and web-accessible tools d Atlas analysis reveals six exRNA cargo types present across five human biofluids d Five of the cargo types associate with specific vesicular and non-vesicular carriers d These findings and resources empower studies of extracellular RNA communication An extracellular RNA atlas from five human biofluids (serum, plasma, cerebrospinal fluid, saliva, and urine) reveals six extracellular RNA cargo types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
261
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 246 publications
(284 citation statements)
references
References 48 publications
(58 reference statements)
12
261
0
2
Order By: Relevance
“…The results, with slightly different composition of large and small bdEVs, suggested that not all small RNAs are uniformly loaded from cells into EVs. Consistent with other reports 13,[38][39][40][41][42] , we also found that fragments of rRNA and tRNA, were more abundant than miRNAs in EVs, even without employing ligation-dependent sequencing library preparation 43 . Although some publications have reported a higher miRNA proportion in EVs 44, 45 than in cells, our results suggested that mapped miRNA reads and diversity gradually decreased from brain homogenate to large EVs and then small EVs.…”
Section: Discussionsupporting
confidence: 92%
“…The results, with slightly different composition of large and small bdEVs, suggested that not all small RNAs are uniformly loaded from cells into EVs. Consistent with other reports 13,[38][39][40][41][42] , we also found that fragments of rRNA and tRNA, were more abundant than miRNAs in EVs, even without employing ligation-dependent sequencing library preparation 43 . Although some publications have reported a higher miRNA proportion in EVs 44, 45 than in cells, our results suggested that mapped miRNA reads and diversity gradually decreased from brain homogenate to large EVs and then small EVs.…”
Section: Discussionsupporting
confidence: 92%
“…However, the contribution of dead cells to□exRNA□profiles is unclear. Although identification of RNAs actively and selectively released to the extracellular space can help to understand physiological communication circuits between nonadjacent cells, nonselective RNA release (derived from either live or dead cells) can provide cell- or tissue-specific extracellular signatures which can be identified, at least in theory, by deconvolution analysis 29 . However, it is reasonable to expect that those exRNAs that are not contained inside EVs would be rapidly degraded by extracellular RNases.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, extracellular miRNAs can have a primary role in cell-to-cell communication, gene expression regulation, and cell reprogramming of target cells, as well as the exploration of the mechanisms of their release in the body fluids, assuming that an escalating focus on these molecules in the course of the last 2 to 3 years continues [37]. Out of total cell-free biofluid RNA, small non-coding RNA species, including miRNAs, are the most abundant in circulation, and are co-purified with both small EVs and non-EV particles [20,38]. A fraction of the functional miRNAs found into the blood are thought to be passively released by dying cells as complexes with RNA-binding proteins (RBPs) or encapsulated within apoptotic bodies [39,40].…”
Section: Content Of Extracellular Vesicles and Functional Role In Nsclcmentioning
confidence: 99%
“…Protein-RNA complexes are necessary to protect circulating miRNAs from plasma RNAases, and AGO2, the same effector of miRNA-mediated silencing [41], can also guide the release in the circulation of a bunch of cellular non-EV associated miRNAs with active biological functions [42]. Cell-released miRNAs can also be transported in the plasma and delivered to recipient cells by other non-vesicular particles, like high-density lipoprotein (HDL) complexes and exomeres [38,43]. However, most of the cell-released miRNAs involved in the direct silencing of cellular mRNAs are selectively delivered to target cells by loading within small EVs [20,38].…”
Section: Content Of Extracellular Vesicles and Functional Role In Nsclcmentioning
confidence: 99%